Cardiorespiratory fitness and cognition in persons at risk for Alzheimer's disease. Issue 1 (8th July 2022) - Vesperman, Clayton J.; Wang, Rui; Schultz, Stephanie A.; Law, Lena L.; Dougherty, Ryan J.; Ma, Yue; Oh, Jennifer M.; Edwards, Dorothy F.; Gallagher, Catherine L.; Chin, Nathaniel A.; Asthana, Sanjay; Hermann, Bruce P.; et al.
Abstract: Introduction: This study examined the relationship between cardiorespiratory fitness (CRF) and longitudinal cognitive functioning in a cohort enriched with risk factors for Alzheimer's disease (AD). Methods: A total of 155 enrollees in the Wisconsin Registry for Alzheimer's Prevention completed repeat comprehensive neuropsychological evaluations that assessed six cognitive domains. Peak oxygen consumption (VO2 peak) was the primary measure of CRF. Random effects regression was used to investigate the effect of CRF on cognitive trajectories. Results: Higher CRF was associated with slower decline in the cognitive domains of verbal learning and memory ( P  < .01) and visual learning and memory ( P  < .042). Secondary analyses indicated that these effects were stronger among men than women, and for noncarriers of the apolipoprotein E ε4 allele. Discussion: Higher CRF was associated with a slower rate of the decline in episodic memory that occurs as a natural consequence of aging in a cohort enriched with risk factors for AD.